The performance of high voltage; outdoor insulation in polluted environments - Macy, R E (Department of Electrical Engineering, 2023)
"An iron wire, 12000 feet in length, was suspended about five feet from the ground by silk cords; one end of it was connected to the globe of an electrical machine, and at the other a lead ball was hung in order to perceive when the matter reached it. After five or six turns of the wheel, the matter had passed along the whole wire and communicated its virtue to the ball, which instantly attracted and repelled light bodies. 2. As this ball was equally electrified with every part of the wire, it is probable that the electric matter would instantly pervade a wire of a still greater length, provided we had a proper apparatus for the purpose. 3. Several metals and other conductors were substituted in place of the ball, and all received the electricity in the same manner. The ball and touched with other non-conductors, :when' the finger, gave a luminous spark and as smart a shock as when the end of the wire next to 'the 'gTobe·vas touched. All these effects instantly ceased whenever .. any person not electrified touched any part of the wire and commenced again a few seconds after his hand was withdrawn. The same effects are produced, though with more difficultly, when hair or woollen ropes were substituted in place of the silk ones: But they were entirely stopped by hemp ropes or when the silk ones were wetted."